Role of innovation in economy development of the world and kazakhstan - TUZUBEKOVA M.K; MEDET, KONYRBEKOV; ALIYA, BIKTEUBAYEVA; ASEM, KOBIYEVA; SANTAY, TLEUBAYEVA; SAGYNKUL, PRALIEVA (The journal of contemporary issues in business and government, 2020)
This article analyzes the modern development of innovative activity, characterized by an increase in the role of its results in the life of mankind, both in spiritual and material production. At a certain stage of innovation, the role of intellectual property depends on the content of work, and, therefore, it is closely related to the structure of the innovation process and the characteristics of its stages.